2021
DOI: 10.1098/rspb.2021.0157
|View full text |Cite
|
Sign up to set email alerts
|

Light environment influences mating behaviours during the early stages of divergence in tropical butterflies

Abstract: Speciation is facilitated when traits under divergent selection also act as mating cues. Fluctuations in sensory conditions can alter signal perception independently of adaptation to the broader sensory environment, but how this fine-scale variation may constrain or promote behavioural isolation has received little attention. The warning patterns of Heliconius butterflies are under selection for aposematism and act as mating cues. Using computer vision, we extracted behavioural data fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 72 publications
4
10
2
Order By: Relevance
“…The results of our experiments with H. timareta may simply reflect the lack of strong differences in visual attraction. In particular, mate choice experiments with H. t. linaresi males – which were run concurrently with experiments reported here – revealed that males show only very weak preferences for the conspecific yellow pattern over a yellow-red pattern, as used in the present study (Hausmann et al 2021). Recently, it has also become apparent that the composite color patterns of H. heurippa may not be the target of differences in male attraction between different species of Heliconius (Mavárez et al 2021).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The results of our experiments with H. timareta may simply reflect the lack of strong differences in visual attraction. In particular, mate choice experiments with H. t. linaresi males – which were run concurrently with experiments reported here – revealed that males show only very weak preferences for the conspecific yellow pattern over a yellow-red pattern, as used in the present study (Hausmann et al 2021). Recently, it has also become apparent that the composite color patterns of H. heurippa may not be the target of differences in male attraction between different species of Heliconius (Mavárez et al 2021).…”
Section: Discussionsupporting
confidence: 67%
“…1B) were collected from Guayabal (2°41’04”N, 74°53’17”W) and H. heurippa (yellow and red forewing bar) from Lejanías (03°34’0”N, 74°04’20.4”W), Buenavista (4°10’30”N, 73°40’41”W) and Santa María (04°53’28.2”N, 73°15’11.4”W) in Colombia. Outbred stocks were established and used to generate H. t. linaresi x H. heurippa F1 and backcrosses to H. t. linaresi hybrids (as described in Hausmann et al 2021). The presence of the red forewing band is controlled by a single Mendelian locus ( optix ), and segregates in the backcross to H. t. linaresi so that equal numbers of individuals display a (‘novel’) yellow-red forewing band phenotype or a (‘control’) yellow forewing phenotype (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…H. timareta linaresi (yellow forewing bar; Figure 1b) were collected from Guayabal (2°41′04″N, 74°53′17″W) and H. heurippa (yellow and red forewing bar) from Lejanías (03°34′0″N, 74°04′20.4″W), Buenavista (4°10′30″N, 73°40′41″W) and Santa María (04°53′28.2″N, 73°15′11.4″W) in Colombia. Outbred stocks were established and used to generate H. t. linaresi × H. heurippa F 1 and backcrosses to H. t. linaresi hybrids (as described in Hausmann et al, 2021). The presence of the red forewing band is controlled by a single Mendelian locus ( optix ), and segregates in the backcross to H. t. linaresi so that equal numbers of individuals display a (novel) yellow‐red forewing band phenotype or a (control) yellow forewing phenotype (Figure 1b).…”
Section: Methodsmentioning
confidence: 99%
“…In other insects, relatively little is known about development and opsin regulation, despite Hymenoptera and Lepidoptera being major visual ecology models [52][53][54]. One key theme to emerge in the last 25 years is the understanding of homology between the inner colour photoreceptor cells between D. melanogaster, Lepidoptera, and Hymenoptera.…”
Section: Opsin Regulation In Other Insectsmentioning
confidence: 99%